The Effect of Posner's Model on Developing The Achievement of Students of The Institute of Fine Arts In The Subject of Art Analysis And Criticism (Journal of the College of Basic Education, 2025)
The research includes knowing "the effect of Posner's model on developing the achievement of students of the Institute of Fine Arts in the subject of art analysis and criticism" It aims to study the effect of Posner's model in correcting artistic misconceptions and improving the level of academic achievement of students of the Institute of Fine Arts. The problem began with identifying that students suffer from difficulty in understanding the material due to traditional teaching methods that focus on memorization and indoctrination. Posner's model is based on the constructivist theory and aims to modify students' misconceptions through four stages: realizing the problem, presenting the new concept, applying it, and finally comprehending it.The results of the research showed that using Posner's model contributed to improving students' academic achievement in the subject of art analysis and criticism. The experimental group (which studied according to this model) showed a clear improvement in achievement compared to the control group, with a statistically significant difference in test results. It was found that the distribution of grades in the experimental group was more homogeneous and less variance, which reflects the effectiveness of the model in correcting misconceptions and enhancing critical and analytical thinking.The results were compared with previous studies, which showed that using interactive models such as Posner can enhance academic achievement and reduce variability in performance among students. The research emphasizes the importance of adopting modern educational strategies, such as Posner’s model, to improve the effectiveness of technical education and guide students towards advanced critical and analytical thinking